2018
DOI: 10.1177/0963689718788521
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of HPV16 E6 mRNA or E7 mRNA Quantitative Expression for Cervical Cells of Patients with Dysplasia and Carcinoma

Abstract: Current human papillomavirus (HPV)16 DNA testing has high sensitivity but low specificity, while mRNA testing (qualitative) improves the specificity. However, both techniques are not able to discriminate between transient and persistent infections. To overcome the disadvantages, we quantitatively detected E6 and E7 mRNAs by quantitative real-time polymerase chain reaction (qRT-PCR) in cervical brushing cells from 87 HPV16+ and 31 HPV16− patients. Our results showed that the expression levels of E6 mRNA or E7 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…15 shown previously to be highly reliable, sensitive, and accurate. 24,25,31 We chose this method to minimize false-negative results and provide clinically relevant reference values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 shown previously to be highly reliable, sensitive, and accurate. 24,25,31 We chose this method to minimize false-negative results and provide clinically relevant reference values.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, 12 types (HPV16, 18,31,33,35,39,45,51,52, 56, 58, and 59) are the etiological agents of cancer, and International Agency for Research on Cancer classified these HPVs as Hr-HPVs. 2 A 2012 study of cervical cancer indicated that 90% of patients with cervical cancer were carrying HPV type 6,11,16,18,31,33,45,52, and/or 58, with 71% of patients carrying types 16 and 18 globally, which are considered to be particularly carcinogenic. 4 HPV exposure is very high, with some 80% of sexually active women acquiring an HPV infection during their lifetimes.…”
Section: Over 200mentioning
confidence: 99%
“…In HPV-positive cervical cancers, all of the malignant cells contain at least one copy of the viral genome with transcriptional activity [7,8]. Recent studies have shown that non-coding microRNAs (miRNAs) are also regulated by E6 and E7 at the transcriptional and post-transcriptional level [6,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence in the literature that the level of the mRNA copies increases proportionally to the severity of the cervical lesion (18). On the contrary, a negative HPV mRNA result in combination with a positive HPV-DNA outcome seems to reflect the presence of an inactive HR-HPV infection with low or absent viral replication.…”
Section: Discussionmentioning
confidence: 98%
“…HPV types:16,18,31, 33, 35, 39, 45, 51, 52, 56, 58, 59, and the probable high-risk type 68 (A and B) as well as the possibly high-risk types 26, 53, 66, 67, 69, 73 and 82 as described by IARC classification from year 2012(9). In the present study, probable and possible HR-HPV types were classified as HR-HPV types.The HPV E6/E7 mRNA (APTIMA) assay (Hologic, Inc.) detects qualitatively E6/E7 mRNA from 14 HR-HPV types:16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 66 and 68.…”
mentioning
confidence: 99%